2007
DOI: 10.1186/1471-213x-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale RNAi screens identify novel genes that interact with the C. elegans retinoblastoma pathway as well as splicing-related components with synMuv B activity

Abstract: Background: The retinoblastoma tumor suppressor (Rb) acts in a conserved pathway that is deregulated in most human cancers. Inactivation of the single Rb-related gene in Caenorhabditis elegans, lin-35, has only limited effects on viability and fertility, yet causes changes in cell-fate and cell-cycle regulation when combined with inactivation of specific other genes. For instance, lin-35 Rb is a synthetic multivulva (synMuv) class B gene, which causes a multivulva phenotype when inactivated simultaneously with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 65 publications
6
103
0
Order By: Relevance
“…S3). Depletion of skr-10 or skr-17 did not lead to lethality in ubc-18 mutant animals, although these genes have been reported to have synthetic genetic interactions with lin-35 that result in larval lethality (21). We also did not observe genetic interactions with skr-8 or skr-9, which suppress the synthetic lethality of ubc-18; lin-35 animals (19).…”
Section: Genetic Interactions Between Ubc-18 and Genes Of The Scf E3mentioning
confidence: 54%
See 1 more Smart Citation
“…S3). Depletion of skr-10 or skr-17 did not lead to lethality in ubc-18 mutant animals, although these genes have been reported to have synthetic genetic interactions with lin-35 that result in larval lethality (21). We also did not observe genetic interactions with skr-8 or skr-9, which suppress the synthetic lethality of ubc-18; lin-35 animals (19).…”
Section: Genetic Interactions Between Ubc-18 and Genes Of The Scf E3mentioning
confidence: 54%
“…The candidate genes that we tested included five Cullins (cul-1, -2, -4, -5, -6) and SKP1-related (skr) and F-box genes chosen based on published genetic and physical interactions with members of the pharyngeal attachment pathway (18)(19)(20)(21). Consistent with previous reports (22), we found that only 25% of WT animals grown on cul-1(RNAi) survived to adulthood, which excluded cul-1(RNAi) from our primary screen.…”
Section: Genetic Interactions Between Ubc-18 and Genes Of The Scf E3mentioning
confidence: 99%
“…1,5 Several genome-wide small interfering RNA (siRNA) screens designed to identify genes with roles in genome maintenance and cell cycle progression have reported a role for spliceosome components in these processes. [6][7][8][9][10][11][12] Mutations in multiple spliceosome subunits have been found in leukemia, myeloid neoplasms, and some solid tumors, 13,14 suggesting that spliceosome defects might promote tumorigenesis perhaps through its roles in genome maintenance and cell division.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale surveys have also been done by injecting in vitro transcribed dsRNAs [20,22] or soaking animals in dsRNA solution [33]. However, as it is technically simpler to deliver dsRNA by feeding, efforts were made to generate libraries of bacterial 'feeding' plasmids that represent each predicted gene [21] or a substantial portion of expressed genes [34]. Many researchers have chosen to use the commercially available library generated by the Ahringer laboratory [21,32].…”
Section: Analysis Of Specific Developmental Processes and Biochemicalmentioning
confidence: 99%